The real-world analysis of adverse events with teduglutide: a pharmacovigilance study based on the FAERS database - Wang, Xiaogan; Chen, Hao; Han, Shuangshuang; Li, Lingbo; Chen, Hongjin; Yang, Bolin (Frontiers in Pharmacology, 2024)
Teduglutide, the first glucagon-like peptide 2 analogue, has been demonstrated to facilitate the absorption of gut nutrient and lessen the need for parenteral assistance in patients with Short Bowel Syndrome (SBS). However, its adverse drug events (AEs) are primarily documented in clinical trials, with a deficit in real-world data. This study evaluates the AEs profile of teduglutide based on Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) data.A disproportionality analysis of FAERS data from Quarter 1 (Q1) 2013 to Quarter 3 (Q3) 2023 was conducted to examine the association between teduglutide and adverse events, employing Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Empirical Bayesian Geometric Mean (EBGM) methods.Out of 13,809,302 reports in the FAERS database, 10,114 reports identified teduglutide as the "primary suspect" in AEs identification. During the dosing observation period, the median occurrence of adverse events was 393 days (interquartile range [IQR] 97-996 days). Teduglutide-associated AEs occurred in 27 System Organ Classes (SOC), of which renal and urinary disorders is not mentioned in the specification. Based on the four algorithms, a total of 260 major disproportionality preferred terms (PTs) were filtered out, including previously unreported AEs including weight decreased (n=805), vascular device infection (n=683), dehydration (n=596) and nephrolithiasis (n=146).Our findings corroborate the AEs listed in the teduglutide prescribing information and additionally unveil new adverse reaction signals such as nephrolithiasis. These discoveries could aid in clinical monitoring and risk identification for teduglutide.